An 18th Century Internet: Modeling Knowledge Organization and Information Retrieval in a Living History Museum - Jank, David (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The purpose of this paper is to examine knowledge organization structures and information access protocols in the Colonial Williamsburg historic restoration in Williamsburg, Virginia. It reports the results of a pilot project designed to provide preliminary models for studying such schema in the interactive learning environment of living history museums. Le but de cet article est d’examine les structures d’organisation de la connaissance et les protocoles d’accès à l’information lors des reconstitutions historiques de Colonial Williamsburg à Williamsburg, en Virginie. Sont présentés les résultats d’un projet pilote conçu pour dégager des modèles préliminaires d’étude de schémas dans l’environnement d’apprentissage interactif que constituent les musées d’histoire vivante.